The Effectiveness of Interactive Snakes and Ladders Game to Improve Arabic Vocabulary Mastery - Lukman, A. M. Khomaeny; Haeriyyah, Haeriyyah; Agussalim, Andi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to evaluate the effectiveness of Snakes and Ladders-based learning media in improving students' mastery of Arabic vocabulary. Traditional methods like textbooks and static visual aids often fail to engage students actively and ensure consistent vocabulary retention. To address this, the study applied a pre-experimental design with a quantitative approach, using a one-group pretest-post-test format. The intervention involved a life-sized Snakes and Ladders board placed on the classroom floor, where students physically moved as game pieces and answered vocabulary prompts at each square—this setup aimed to provide an interactive learning experience, reinforcing vocabulary through repetition and contextual application. The study involved 18 fourth-grade students, with an initial average pretest score of 71.61, which increased to 94.11 in the Post-test, showing an improvement of 22.50 points. A paired t-test revealed a statistically significant improvement (t(17) = -12.144, p < 0.001), with Cohen's d = 3.79, indicating a substantial impact. These results demonstrate that Snakes and Ladders game-based learning can significantly enhance vocabulary acquisition. Incorporating physical movement, peer interaction, and visual stimuli is vital in reinforcing vocabulary retention, offering a promising alternative teaching method to support Arabic language learning at the elementary level.